2010
DOI: 10.1111/j.1365-3180.2010.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of weed seeds subjected to sheep rumen digestion

Abstract: Haidar MA, Gharib C & Sleiman FT (2010). Survival of weed seeds subjected to sheep rumen digestion. Weed Research50, 467–471. Summary An experiment was conducted to examine the effect of sheep rumen digestion on the viability of the seeds of eight weed and two crop species common in Lebanon. Seed samples were put in small monofilament polyester bags and placed in the rumen of fistulated sheep for 1, 2, 3 and 4 days. The viability of the seeds 4 days after placement in the rumen was 85% for Cuscuta campestris, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…The treatment with 0 hours of rumen incubation takes only the in vitro digestion into account, which has no biological meaning, but this treatment shows that this part of the digestive tract of a cow also plays a role in an increase in the germination, but showed only minor effects on seed viability. Our results show a limited effect of digestion (only for the Rms population), which could be explained by the hard seed coat (Haidar et al ., ), acting as a protective layer against microbial and digestive enzymes. Other studies, however, reported higher reductions in viability for C. album after a 24‐h ruminal digestion (Blackshaw & Rode, ).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment with 0 hours of rumen incubation takes only the in vitro digestion into account, which has no biological meaning, but this treatment shows that this part of the digestive tract of a cow also plays a role in an increase in the germination, but showed only minor effects on seed viability. Our results show a limited effect of digestion (only for the Rms population), which could be explained by the hard seed coat (Haidar et al ., ), acting as a protective layer against microbial and digestive enzymes. Other studies, however, reported higher reductions in viability for C. album after a 24‐h ruminal digestion (Blackshaw & Rode, ).…”
Section: Discussionmentioning
confidence: 99%
“…The seeds of the different species (Table ) were placed in bags made from white polyester monofilament (53 ± 10 μm pore size) of the type used for in sacco degradability studies (Bar Diamond ® ). The pore size was small enough to contain all the seeds but still allow for the passage of water, gases and microorganisms through the mesh (Haidar et al ., ). Separate bags were used for each weed species and there were 50 seeds per bag.…”
Section: Methodsmentioning
confidence: 97%
“…Benth. (rice vampire weed) (Rodenburg et al ., ), the passage of weed seeds through sheep (Haidar et al ., ), using dogs to find alien invasive weed plants (Mclean & Sargisson, ) and using drones for weed mapping (e.g. Lambert et al ., ).…”
mentioning
confidence: 99%